Rates and prospective psychosocial correlates of pre-loss grief in cancer and dementia family members. (June 2022) - Singer, Jonathan; Shrout, M. Rosie; Papa, Anthony
This study examined changes in Pre-Loss Grief (PLG) among individuals whose family member has a life limiting illness and how baseline psychosocial factors predicted PLG. This two-wave study recruited family members of advanced cancer ( N = 100) and dementia ( N = 38) patients. A subsample completed 1-month follow-up (Cancer = 33; Dementia = 28). Higher caregiver burden and female participants predicted greater PLG at follow-up, accounting for baseline PLG. Family members of dementia patients (10.5%) were significantly more likely than family members of cancer patients (2.1%) to be in the "severe PLG" group. Findings demonstrate psychosocial factors related to PLG, informing interventions aimed at reducing PLG.